Synergistic Organic Wick and Nutrient Levels on The Morphological Performance of Pakcoy (Brassica rapa L.) in Hydroponic Axis System - Shinta Hanif Nur Edditya; Nova Triani; Juli Santoso (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Pakcoy (Brassica rapa) production in Indonesia continues to rise, reaching 635,982 tons in 2018 and 652,723 tons in 2019. Improper irrigation often causes wilting and root rot. The wick hydroponic system offers a viable alternative but is suitable mainly for crops requiring limited water. Inorganic fertilizers enhance growth and yield, their long-term use poses environmental and human health risks. Organic fertilizers provide a sustainable solution without leaving harmful residues. Optimizing pakcoy cultivation in hydroponic systems requires selecting an appropriate wick material and the optimal concentration of organic fertilizer to achieve sustainable productivity. Methodology: This research was conducted with factorial experiment using a 2-factor completely randomized design, the first factor is the fertilizer concentration treatment consisting of 4 types (N0: AB Mix 3 ml/L-control, N1: LOF 6 ml/L, N2: LOF 9 ml/L, N3: LOF 12 ml/L) and the second factor is the type of wick treatment consisting of 4 types (S0: Flannel cloth wick-control, S1: Coconut fiber wick, S2: Bamboo fiber wick, S3: Banana stem wick). If the results obtained have significant, then continue the 5% DMRT test. Findings: The combined treatment of AB Mix at 3 ml/L and a coconut fiber wick exerted a significant influence on plant height between 15 and 25 DAP (13.37 cm), as well as on several yield parameters at 30 DAP, including crown fresh weight (17.97 g), root fresh weight (3.60 g), total fresh weight (21.57 g), and weight loss (0.24 g). The coconut fiber organic wick independently produced significant effects across all observed parameters, except for the number of leaves recorded at 5 DAP. Overall, the interaction between AB Mix at 3 ml/L and the coconut fiber wick demonstrated effective in enhancing the performance of pakcoy (B. rapa L.) compared with other treatment combinations. Contribution: This study provides valuable insights into optimizing the combination of fertilizer concentration and organic wick type in wick hydroponic systems to enhance the sustainable performance growth of pakcoy while promoting the utilization of environmentally friendly local materials